A New Writing of the Arrapḫa Place Name URU.Turzanzi / Dūrzanzi - Fincke, Jeanette
EN 10/1, 38 Joined to HSS 13, 300: ebd. 425-426; One Fragment from NTF P 181 Joined to HSS 15, 26: ebd. 426-428; HSS 19, 108 Joined to EN 9/1, 139: ebd. 428-429; Two Fragments from NTF P 2 and 'Clay bullae' nos. 770 and 772 Joined to EN 9/2, 16: ebd. 429-